Effect of different organic sources on productivity and quality of pearlmillet (Pennisetum glaucum) and their residual effect on wheat (Triticum aetivum) - Bana, R.S.; Gautam, R.C.; Rana, K.S. (Annals of Agricultural Research, 2014)
A field experiment was conducted during 2004-05 and 2005-06 at Indian Agricultural Research Institute, New Delhi to study the effect of different organic sources of nutrients on productivity and quality of pearlmillet (Pennisetum glaucum L. R. Br. Emend Stuntz) and to study the residual effect of various treatments on succeeding crop of wheat (Triticum aetivum L.). The experiment comprised eight treatments viz. control, Biofertilizer (Azospirillum + PSB), FYM (10 t/ha) + biofertilizer (Azospirillum+ PSB), Vermicompost (10 t/ha) + biofertilizer (Azospirillum + PSB), Sesbania leaf manuring + biofertilizer (Azospirillum + PSB), FYM (10 t/ha) + legume intercropping, Vermicompost (10 t/ha) +legume intercropping and Sesbania leaf manuring + legume intercropping. Different organic sources showed considerable increase in growth components, yield and quality of pearlmillet. Vermicompost (10 t/ha) + biofertilizer produced the highest pearlmillet grain yield, that is 2.18 and 2.04 t/ha during 2004 and 2005 respectively; and had maximum residual effect on wheat yield.